2006
DOI: 10.1002/sim.2692
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study comparing properties of heterogeneity measures in meta‐analyses

Abstract: The assessment of heterogeneity or between-study variance is an important issue in meta-analysis. It determines the statistical methods to be used and the interpretation of the results. Tests of heterogeneity may be misleading either due to low power for sparse data or to the detection of irrelevant amounts of heterogeneity when many studies are involved. In the former case, notable heterogeneity may remain unconsidered and an unsuitable model may be chosen and the latter case may lead to unnecessary complex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 30 publications
2
101
0
3
Order By: Relevance
“…In practice, max{0, I 2 } and maxf0; H 2 M g are used to restrict the ranges of these measures as positive. As the simulation study of Mittlbock and Heinzl, 59 unrestricted values of I 2 and H 2 M were used to obtain unbiased distributions for these measures in this study. These two measures presented monotonic increases as t 2 increased.…”
Section: Simulation Studymentioning
confidence: 99%
“…In practice, max{0, I 2 } and maxf0; H 2 M g are used to restrict the ranges of these measures as positive. As the simulation study of Mittlbock and Heinzl, 59 unrestricted values of I 2 and H 2 M were used to obtain unbiased distributions for these measures in this study. These two measures presented monotonic increases as t 2 increased.…”
Section: Simulation Studymentioning
confidence: 99%
“…Reporting of these items may reduce the level of bias in randomized clinical trials. Furthermore, bias between randomized controlled studies in metaanalyses may also be caused by heterogeneity of the research designs of the studies, such as different therapeutic dosages or exercise strategies [27].…”
Section: Methodological Qualitymentioning
confidence: 99%
“…I 2 is deemed to be more reliable in assessing inconsistency between studies, with values of 25%, 50% and 75% corresponding to low, moderate and high heterogeneity respectively (Higgins, Thompson, Deeks, and Altman 2003). only measure that is truly independent of k and it takes values in the [0, +∞) range with 0 indicating -a somewhat worrying -perfect homogeneity (Mittlbock and Heinzl 2006). It has also been suggested that the estimate of between-study variance,τ 2 , should be reported (Higgins and Green 2008), therefore the estimated between-study variance, where relevant to the model, is also displayed.…”
Section: Meta-analysis Methods Overviewmentioning
confidence: 99%